Personal Digital Storyworlds, Narrative Architects, and Gmail - Zalinger, Jason (AoIR Selected Papers of Internet Research, 2013)
New technologies change the recording of our life stories. They challenge us to make a coherent picture from so many digital puzzle pieces. Online, we have been given a rich variety of what I call $2 and seemingly unlimited space to collect personal data. However, we have not given users the conceptual and practical tools to help people create cohesive, meaningful life narratives out of all these digital fragments. Bottom line: we are very good at capturing data, but we are not good, yet, at helping people make sense of all these digital narrative elements. This paper asks the audience to reimagine Gmail as a storyworld. The goal is to provide new insights that advance academic conversations about personal digital archives, which will become an essential element of Web 3.0. Using data from participant interviews, this paper makes the case that personal digital archives produce meaningful, conflicting emotions in people, and they provide insight into how technology shapes how we understand ourselves.